2021
DOI: 10.1073/pnas.2016569118
|View full text |Cite
|
Sign up to set email alerts
|

Communicating artificial neural networks develop efficient color-naming systems

Abstract: Words categorize the semantic fields they refer to in ways that maximize communication accuracy while minimizing complexity. Focusing on the well-studied color domain, we show that artificial neural networks trained with deep-learning techniques to play a discrimination game develop communication systems whose distribution on the accuracy/complexity plane closely matches that of human languages. The observed variation among emergent color-naming systems is explained by different degrees of discriminative need,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 47 publications
2
24
1
Order By: Relevance
“…An example is a recent demonstration that colors in a visual scene are efficiently expressed by language. This was shown in an artificial neural network [39]. This shows evidence for efficiency in the neural coding of information and that artificial models emulate this efficiency.…”
Section: Cognition As a Physiological Processmentioning
confidence: 58%
“…An example is a recent demonstration that colors in a visual scene are efficiently expressed by language. This was shown in an artificial neural network [39]. This shows evidence for efficiency in the neural coding of information and that artificial models emulate this efficiency.…”
Section: Cognition As a Physiological Processmentioning
confidence: 58%
“…The fact that the current categorical representation appears to emerge in the absence of color naming emphasizes that explicit color naming is not a necessity for the development of categories. This may seem to stand in contrast to many of the recent studies that use communicative concepts as a means to model the shape of categories (Chaabouni et al, 2021;Gibson et al, 2017b;Twomey et al, 2020;Zaslavsky et al, 2020). However, many of those studies derive their predictive power from combining these concepts with the nonuniformities in the utility across colors.…”
Section: Discussionmentioning
confidence: 74%
“…While the degree of importance for communication in shaping categories varies, many of these recent studies rely on communicative concepts when it comes to shaping color categories. Notably, a recent study where communicating deep neural networks played a discrimination game demonstrated that allowing continuous message passing made the emergent system more complex complex and decreased efficiency (Chaabouni, Kharitonov, Dupoux, & Baroni, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Similar adaptation and efficiency effects have also been observed in experimental settings with artificial languages (cf. Chaabouni, Kharitonov, Dupoux, & Baroni, 2021; Fedzechkina, Jaeger, & Newport, 2012; Guo et al., 2021; Nölle, Staib, Fusaroli, & Tylén, 2018; Tinits, Nölle, & Hartmann, 2017; Winters, Kirby, & Smith, 2015).…”
Section: Introductionmentioning
confidence: 99%